Composite positive electrode slurry, positive electrode and preparation method thereof

The structural integrity and conductivity of traditional binders under high pressure were solved by using hydrogenated nitrile rubber latex (HNBR) as a dispersant for binders and CNTs, combining lithium manganese iron phosphate and high nickel ternary layered oxides. The problem of insufficient improvements in the energy density and cycle stability of lithium-ion batteries, extends battery life and reduces safety risks.

CN119133455APending Publication Date: 2024-12-13SHANGHAI LIANKE NEW MATERIALS CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411270377.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional PVDF binders are difficult to maintain the structural integrity and electron/ion conduction capability of the positive electrode material under high pressure, resulting in insufficient energy density and cyclic stability of lithium-ion batteries and pose safety risks.

Method used

Hydrogenated nitrile rubber latex (HNBR) is used as the binder, combining lithium manganese iron phosphate and high nickel ternary layered oxides, and the adhesion of the binder is improved through the strong coordination effect of HNBR and the uniform dispersion of CNT. and conductivity, enhance the cohesion and external convergence of the cathode material, and improve charge transport capability.

Benefits of technology

It improves the stability and cycle times of the positive electrode material, extends the battery life, enhances the energy density and high-voltage cycle stability of lithium-ion batteries, and reduces the risk of side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133455A_ABST
    Figure CN119133455A_ABST
Patent Text Reader

Abstract

The invention provides composite positive electrode slurry, a positive electrode and a preparation method thereof, and relates to the field of lithium batteries. The solid content of the slurry is 40-60wt%, and the slurry comprises the following raw materials in parts by weight: 1-5 parts of a binder, 2-4 parts of a conductive agent, 100 parts of a blended positive electrode active material and the balance of a solvent; the binder comprises hydrogenated butadiene-acrylonitrile rubber emulsion, and the mass fraction of the hydrogenated butadiene-acrylonitrile rubber emulsion combined with acrylonitrile is 10-50%; the blending type positive electrode active material comprises the following components in percentage by mass: 10-90% of lithium manganese iron phosphate and 10-90% of high-nickel ternary layered oxide. The positive electrode comprises an aluminum foil current collector and composite positive electrode slurry, and the composite positive electrode slurry is coated on the surface of the aluminum foil current collector. According to the present invention, the positive electrode of the positive electrode slurry composed of the HNBR binder, the conductive agent and the solvent is combined with the blending type positive electrode active material composed of the lithium manganese iron phosphate and the high-nickel ternary layered oxide, and the positive electrode is applied to the lithium ion secondary battery, and the battery has high energy density and high-voltage cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a composite positive electrode slurry, a positive electrode and a preparation method thereof. Background Art

[0002] The energy density of lithium-ion batteries depends largely on its cathode material. Lithium iron manganese phosphate and high-nickel ternary layered oxide cathode materials have been widely used due to their superior operating voltage window and high reversible specific capacity. Lithium iron manganese phosphate and high-nickel ternary layered oxide blended cathode materials have the advantages of both. They not only have higher energy density, but also have better cycle stability and safety, and their cost is relatively low. However, with the increase in demand for driving range, lithium-ion batteries still have the defect of low energy density. High-voltage cathode materials are the basis of high energy density batteries.

[0003] As an important component of the positive electrode, the binder plays a vital role in maintaining the integrity of the mechanical and ionic / electronic conductivity between the active material particles, the conductive agent and the current collector, and can minimize the structural damage to the positive electrode during the battery cycle. The traditional PVDF (polyvinylidene fluoride) binder is difficult to operate under high pressure in the blended positive electrode material. The reason is that PVDF has a weak interaction with TM ions (transition metal ions) and has a poor ability to inhibit the dissolution of TM ions, especially Mn in the lithium manganese iron phosphate positive electrode material during the charge and discharge process. 3+ The PVDF is an electrical insulator in its original state and can only transfer charge through a certain amount of liquid electrolyte expansion, which is not conducive to the rapid conduction of electrons / ions during high-voltage cycles. The weak van der Waals force of the linear PVDF binder is not enough to prevent the formation of intracrystalline cracks and maintain the structural integrity of the positive electrode material, especially for lithium-ion batteries with high active material loads used in industrial applications. At the same time, PVDF has limited ability to suppress serious side reactions of positive electrode materials under high pressure, especially for high-nickel ternary layered oxide positive electrode materials with more surface active Ni in the charged state. 4+ It will interact with the electrolyte, posing safety risks of violent gas production and thermal runaway. Summary of the invention

[0004] The object of the present invention is to provide a composite positive electrode slurry, in which the binding strength between the binder and the transition metal ions in the active material is high and the stability of the active material is good.

[0005] Another object of the present invention is to provide a method for preparing a composite positive electrode slurry. The positive electrode slurry obtained by the method has good stability and long service life.

[0006] The third object of the present invention is to provide a positive electrode, which has a high number of cycles in a lithium battery and a long life, and a lithium battery containing the positive electrode has a high energy density and high-voltage cycle stability.

[0007] The present invention solves the technical problem by adopting the following technical solutions.

[0008] On the one hand, an embodiment of the present invention provides a composite positive electrode slurry, wherein the solid content of the slurry is 40-60wt%, and the slurry includes the following raw materials in parts by weight: 1-5 parts of a binder, 2-4 parts of a conductive agent, 100 parts of a blended positive electrode active material, and the balance is a solvent;

[0009] The binder comprises hydrogenated nitrile rubber emulsion, and the mass fraction of the combined acrylonitrile is 15-35%. The mixed positive electrode active material comprises, by mass fraction, 10-90% of lithium manganese iron phosphate and 10-90% of high-nickel ternary layered oxide.

[0010] In some embodiments of the present invention, the following raw materials are included, by weight: 2-4 parts of a binder, 2-4 parts of a conductive agent, 100 parts of a blended positive electrode active material, and the remainder is a solvent.

[0011] The strong coordination effect of -C≡N- in the HNBR binder can provide sufficient cyanide to coordinate lithium ions to improve the ion transfer rate, and can enhance the interaction with TM ions to reduce the dissolution of TM ions in the electrolyte, while improving the adhesion of the binder to enhance the cohesion between the active materials and the cohesion between the active materials and the current collector; in addition, the use of HNBR dispersant in the CNT solution can make the CNTs evenly dispersed in the positive electrode slurry, so as to better play the role of the conductive agent and improve the charge transfer capacity.

[0012] In some embodiments of the present invention, the solvent is N-methylpyrrolidone.

[0013] In some embodiments of the present invention, the weight average molecular weight of the hydrogenated nitrile rubber latex as the binder is 100,000-1,000,000 g / mol, the Mooney viscosity is 20-100 ML (1+4) 100° C., and the unsaturation is 0.1-10%.

[0014] In some embodiments of the present invention, the weight average molecular weight of the hydrogenated nitrile rubber latex as the binder is 300,000-700,000 g / mol, the Mooney viscosity is 40-80 ML (1+4) 100° C., and the unsaturation is 0.1-5%.

[0015] In some embodiments of the present invention, the rotational viscosity of the binder is 1000-20000 mPa·S. Preferably, the rotational viscosity of the binder is 2000-10000 mPa·S.

[0016] In some embodiments of the present invention, the conductive agent comprises carbon black, carbon nanotubes and a dispersant, wherein the mass percentage of the carbon nanotubes is 2-20%, and the mass ratio of the dispersant to the carbon nanotubes is 5-50:100. Preferably, the mass percentage of the carbon nanotubes is 5-10%, and the mass ratio of the dispersant to the carbon nanotubes is 5-20:100.

[0017] In some embodiments of the present invention, the mass percentage of the carbon nanotubes is 5-10%, and the mass ratio of the dispersant to the carbon nanotubes is 5-20:100.

[0018] In some embodiments of the present invention, the average diameter of the carbon nanotubes is 1-30 nm, and the BET specific surface area of ​​the carbon nanotubes is 100-300 m 2 / g.

[0019] In some embodiments of the present invention, the dispersant is a hydrogenated nitrile rubber emulsion, which has a combined acrylonitrile mass fraction of 5-40%, a weight average molecular weight of 50000-600000 g / mol, a Mooney viscosity of 10-80 ML (1+4) 100°C, and an unsaturation of 0.1-10%. The rotational viscosity of the conductive agent dispersion is 500-10000 mPa·S.

[0020] In some embodiments of the present invention, the dispersant is a hydrogenated nitrile rubber emulsion, the mass fraction of the combined acrylonitrile is 10-30%, the weight average molecular weight is 100000-400000 g / mol, the Mooney viscosity is 20-60 ML (1+4) 100°C, and the unsaturation is 0.1-5%. The rotational viscosity of the conductive agent dispersion is 500-5000 mPa·S

[0021] CNT (carbon nanotube) and conductive agent can improve the charging rate of active materials, and can also inhibit the growth of internal resistance of batteries when used in small amounts. Using HNBR as a dispersant for the conductive agent, preparing CNT and conductive agent into a dispersion can overcome the problem of unevenness and partial agglomeration of CNT and conductive agent in the slurry due to low solubility and low dispersibility. Compared with the high hygroscopicity of the traditional dispersant PVP (vinyl pyrrolidone), it is easy to absorb moisture in the air and cause the active material in the electrode slurry to deteriorate. PVP dispersant also has the disadvantage that its electrical insulation is not conducive to charge transfer. Using HNBR instead of PVP can overcome the above problems, and the resulting electrode slurry has good dispersibility and long service life.

[0022] In some embodiments of the present invention, the molecular formula of the lithium manganese iron phosphate is LiFe a Mn 1-a PO 4, where 0<a≤0.5; the molecular formula of high nickel ternary layered oxide is LiNi b Co c Mn 1-b-c O 2 , where 0.6≤b<1, 0<c≤0.2, and b+c<1.

[0023] On the other hand, an embodiment of the present invention provides a method for preparing a composite positive electrode slurry, wherein a binder, a conductive agent, a blended positive electrode active material and a solvent are mixed and dispersed by stirring to obtain the composite positive electrode slurry; wherein the stirring speed is 1000-3000rpm, and the stirring time is 1-5min.

[0024] The third invention, an embodiment of the present invention provides a positive electrode, including an aluminum foil current collector and the above-mentioned composite positive electrode slurry, the composite positive electrode slurry is coated on the surface of the aluminum foil current collector to form a slurry layer.

[0025] In some embodiments of the present invention, the coating rate of the composite positive electrode slurry on the aluminum foil current collector is 2-10 m / min, and the coating thickness is 50-200 μm. Preferably, the coating rate is 4-8 m / min, and the coating thickness is 60-150 μm.

[0026] In a fourth aspect, the present invention provides a method for preparing a positive electrode, wherein the composite cloth slurry is coated on one side of an aluminum foil current collector using a coating machine to form a positive electrode active material layer; the coated electrode piece is placed in a vacuum oven for drying to obtain a positive electrode electrode piece. The vacuum drying temperature is 80-140°C and the time is 8-20 hours. Preferably, the vacuum drying temperature is 100-120°C and the time is 10-15 hours.

[0027] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0028] The composite positive electrode slurry provided by the present invention uses hydrogenated nitrile rubber (HNBR) as a binder, a blend of lithium iron manganese phosphate and a high-nickel ternary layered oxide as a positive electrode active material, and uses HNBR to replace the traditional PVDF binder. The HNBR binder has excellent charge transfer capability, electrochemical compatibility and mechanical strength. On the one hand, the HNBR binder can provide enough cyano groups to coordinate lithium ions, thereby improving the ion transfer rate; on the other hand, the cyano groups (-C≡N-) of the HNBR binder will have a strong coordination bond interaction with transition metal ions (such as manganese, nickel ions in the active material), which can be used as electron donors and electron acceptors, respectively, increasing the energy barrier of irreversible migration of transition metal ions to lithium vacancies, and reducing the dissolution of transition metal ions in the electrolyte; at the same time, the strong coordination bond enhances the adhesion of the binder, improves the cohesion between the active materials, and the cohesion between the active materials and the current collector, that is, improves the peel strength of the positive electrode slurry.

[0029] A blended positive electrode active material of lithium manganese iron phosphate and high nickel ternary layered oxide, combined with a positive electrode slurry of an HNBR binder, a conductive agent and a solvent, is applied to a lithium ion secondary battery, and the battery has high energy density and high-voltage cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 This is a positive electrode sheet peeling curve diagram of Example 1 of the present invention;

[0032] Figure 2 This is a positive electrode sheet peeling curve diagram of Example 3 of the present invention;

[0033] Figure 3 This is a positive electrode sheet peeling curve diagram of Example 4 of the present invention;

[0034] Figure 4 This is a positive electrode sheet peeling curve diagram of Example 7 of the present invention;

[0035] Figure 5 This is a positive electrode sheet peeling curve diagram of Example 13 of the present invention;

[0036] Figure 6 This is a positive electrode sheet peeling curve diagram of Comparative Example 1 of the present invention; DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0038] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0039] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0040] Example 1

[0041] (1) Preparation of positive electrode slurry

[0042] 420 mg of 8% HNBR binder solution (pre-dispersion solution with N-methylpyrrolidone as solvent), 875 mg of CNT conductive agent solution with HNBR as dispersant, and 35 mg of Super-P conductive agent powder were added into a stirring cup and placed into a THINKY stirring and degassing machine at a speed of 2000 rpm for 2 minutes; 420 mg of HNBR binder solution was continued to be added at a speed of 2000 rpm for 2 minutes; then 1.1 g of lithium manganese iron phosphate and 1.1 g of high-nickel ternary layered oxide positive electrode active material were added at a speed of 1500 rpm for 2.5 minutes to obtain a positive electrode slurry.

[0043] Among them, when HNBR is used as a binder, its combined acrylonitrile mass fraction is 20%, the weight average molecular weight is 400000 g / mol, the Mooney viscosity is 50ML(1+4)100°C, and the unsaturation is 0.5%; the combined acrylonitrile mass fraction of HNBR dispersant is 12%, the weight average molecular weight is 200000 g / mol, the Mooney viscosity is 30ML(1+4)100°C, and the unsaturation is 0.5%;

[0044] The solid content of the CNT conductive agent solution is 4% (ie, CNT+HNBR+other additives are 4%), and N-methylpyrrolidone is the solution, accounting for 96%.

[0045] The mass ratio of lithium manganese iron phosphate and high nickel ternary layered oxide is 1:1, and the molecular formula of lithium manganese iron phosphate is LiFe 0.5 Mn 0.5 PO 4 , the molecular formula of high nickel ternary layered oxide is LiNi 0.8 Co 0.1 Mn 0.1 O 2 In other embodiments of the present invention, lithium manganese iron phosphate and high nickel ternary layered oxides of other molecular formulas may also be used.

[0046] (2) Preparation of positive electrode sheet

[0047] The mixed positive electrode slurry was coated on a 20μm thick aluminum foil current collector using an automatic coating machine to a coating thickness of 120μm, and then placed in a 120℃ vacuum oven for drying for 12h. The dried positive electrode sheet was rolled with a roller press at a pressure of 120t, and the rolled sheet was cut into 4.1×6.3cm pieces using a sheet slitting machine. 2 Size, that is, the positive electrode is obtained.

[0048] (3) Preparation of secondary batteries

[0049] Using porous polypropylene as separator, LiPF 6 (Composition: 1.2M LiPF 6 , ethylene carbonate EC: ethyl methyl carbonate EMC = 3:7, + 2% VC) as the electrolyte, commercial graphite (graphite: Super-P: CMC: SBR = 94:3:1.5:1.5) as the negative electrode. The separator is set between the positive and negative electrode sheets, and the battery is assembled using a stacking method. The above electrolyte is injected into the assembled battery to obtain a secondary battery system.

[0050] Example 2

[0051] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the mass ratio of the positive electrode active material lithium manganese iron phosphate and the high nickel ternary layered oxide was 3:7.

[0052] Example 3

[0053] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the mass ratio of the positive electrode active material lithium manganese iron phosphate and the high nickel ternary layered oxide was 7:3.

[0054] Example 4

[0055] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the mass ratio of the positive electrode active material lithium manganese iron phosphate and the high nickel ternary layered oxide was 1:9.

[0056] Example 5

[0057] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the mass ratio of the positive electrode active material lithium manganese iron phosphate and the high nickel ternary layered oxide was 9:1.

[0058] Example 6

[0059] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the mass fraction of bound acrylonitrile in HNBR used as a binder was 15%.

[0060] Example 7

[0061] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the mass fraction of bound acrylonitrile in HNBR used as a binder was 30%.

[0062] Example 8

[0063] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the weight average molecular weight of HNBR used as a binder was 200,000 g / mol.

[0064] Example 9

[0065] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the weight average molecular weight of HNBR used as a binder was 700,000 g / mol.

[0066] Example 10

[0067] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the mass fraction of bound acrylonitrile in HNBR used as a dispersant was 10%.

[0068] Embodiment 11

[0069] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the mass fraction of bound acrylonitrile in HNBR used as a dispersant was 16%.

[0070] Example 12

[0071] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the weight average molecular weight of HNBR used as a dispersant was 100,000 g / mol.

[0072] Example 13

[0073] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the weight average molecular weight of HNBR used as a dispersant was 300,000 g / mol.

[0074] Comparative Example 1

[0075] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the binder was PVDF and the dispersant in the CNT solution was PVP.

[0076] Comparative Example 2

[0077] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the binder was PVDF.

[0078] Comparative Example 3

[0079] A positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the dispersant in the CNT solution was PVP.

[0080] Experimental example

[0081] 1. Peel strength test of positive electrode

[0082] The positive electrode sheets prepared in Examples 1-13 and Comparative Examples 1-3 were cut into 8×2.5 cm strips, and the strips were pasted on organic glass plates. One end of the strips was attached to the strips using 3M transparent tape. The other ends of the organic glass plates and 3M transparent tape were respectively fixed to the upper and lower clamps of a universal tensile testing machine, and the strips were subjected to a 180° peel strength test at a tensile rate of 10 mm / min. The results are shown in Table 1.

[0083] 2. Cycle performance test of secondary batteries

[0084] The secondary batteries prepared in Examples 1-13 and Comparative Examples 1-3 were used as test objects. The secondary batteries were cycled at 1C rate at 25°C and 2.7-4.5V voltage window, and the capacity retention rate after 500 cycles was recorded. Wherein, capacity retention rate (%) = (500th cycle discharge capacity / 1st cycle discharge capacity) × 100%. The results are shown in Table 1.

[0085] Table 1 Test results of Examples 1-13 and Comparative Examples 1-3

[0086]

[0087]

[0088] It can be concluded from the test results in Table 1 that the positive electrode sheets of Examples 1-13 of the present invention have higher peel strength than those of Comparative Examples 1-3, indicating that the bonding strength between the positive electrode slurry and the current collector is high. During use, the bonding strength between the lithium manganese iron phosphate and high nickel ternary layered oxide active materials on the positive electrode sheets and the aluminum foil current collector is high. During the charge and discharge process, the active materials are not easily dissolved into the electrolyte, the loss of active materials is small, the battery has high energy density, and good cycle stability.

[0089] In Examples 1-5, different proportions of lithium iron manganese phosphate and high nickel ternary layered oxides correspond respectively. It can be seen from the data in Table 1 that the peeling strength, battery mass energy density, and battery capacity retention rate of lithium iron manganese phosphate and high nickel ternary layered oxides with different ratios are also different. When there are more high nickel ternary layered oxides, there will be a high battery energy density, but the battery capacity retention rate will be reduced. When the content of lithium iron manganese phosphate is high, the battery capacity retention rate is high, while the peeling strength and battery mass energy density are relatively poor. When the ratio of the two is 1:1 (Example 1), the peeling strength, battery mass energy density, and battery capacity retention rate are all excellent.

[0090] The binder used in Comparative Example 1 is PVDF, and the dispersant in the CNT solution is PVP. Its battery-level capacity retention rate is worse than that of Example 1, and the battery mass energy density and the peel strength of the pole piece are also worse than those of Example 1. Similarly, the positive electrode peel strength and battery performance of Comparative Examples 2 and 3 are worse than those of Example 1. It can be seen that the use of HNBR as a binder and dispersant in Example 1 can improve the peel strength of the positive electrode material, and the active material in the positive electrode sheet is difficult to dissolve in the electrolyte, the positive electrode sheet has a long service life, and the battery capacity retention rate is high.

[0091] As attached Figure 1-6 As shown, the positive electrode sheet peeling strength curves of Examples 1.3.4.7.13 and the comparative example are shown. It can be concluded from the figure that the bonding strength will gradually increase with the increase of the proportion of high-nickel ternary.

[0092] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A composite positive electrode slurry, characterized in that: The slurry has a solid content of 40-60wt%, and comprises the following raw materials in parts by weight: 1-5 parts of binder, 2-4 parts of conductive agent, 100 parts of blended positive electrode active material, and the balance is solvent; The binder comprises hydrogenated nitrile rubber emulsion, and the mass fraction of the combined acrylonitrile is 10-50%; The mixed positive electrode active material comprises, by mass fraction, 10-90% of lithium manganese iron phosphate and 10-90% of high-nickel ternary layered oxide.

2. The composite positive electrode slurry according to claim 1, characterized in that: The hydrogenated nitrile rubber emulsion has a weight average molecular weight of 100,000-1,000,000 g / mol, a Mooney viscosity of 20-100 ML (1+4) 100° C., and an unsaturation degree of 0.1-10%.

3. The composite positive electrode slurry according to claim 1, characterized in that: The rotational viscosity of the binder is 1000-20000 mPa·S.

4. The composite positive electrode slurry according to claim 1, characterized in that: The conductive agent comprises carbon black, carbon nanotubes and a dispersant, wherein the mass percentage of the carbon nanotubes is 2-20%, and the mass ratio of the dispersant to the carbon nanotubes is 5-50:

100.

5. The composite positive electrode slurry according to claim 4, characterized in that: The average diameter of the carbon nanotubes is 1-30 nm, and the BET specific surface area of ​​the carbon nanotubes is 100-300 m 2 / g.

6. The composite positive electrode slurry according to claim 4, characterized in that: The dispersant is hydrogenated nitrile rubber emulsion, the mass fraction of combined acrylonitrile is 5-40%, the weight average molecular weight is 50000-600000 g / mol, the Mooney viscosity is 10-80 ML (1+4) 100 DEG C, and the unsaturation is 0.1-10%.

7. The composite positive electrode slurry according to claim 1, characterized in that: The molecular formula of the lithium manganese iron phosphate is LiFe a Mn 1-a PO4, where 0<a≤0.5; The molecular formula of high nickel ternary layered oxide is LiNi b Co c Mn 1-b-c O2, wherein 0.6≤b<1, 0<c≤0.2, and b+c<1.

8. A method for preparing a composite positive electrode slurry according to any one of claims 1 to 7, characterized in that: The process comprises mixing and dispersing a binder, a conductive agent, a blended positive electrode active material and a solvent by stirring to obtain the composite positive electrode slurry; wherein the stirring speed is 1000-3000 rpm and the stirring time is 1-5 minutes.

9. A positive electrode, characterized in that: It comprises an aluminum foil current collector and the composite positive electrode slurry according to any one of claims 1 to 7, wherein the composite positive electrode slurry is coated on the surface of the aluminum foil current collector.

10. The positive electrode according to claim 9, characterized in that The coating rate of the composite positive electrode slurry on the aluminum foil current collector is 2-10 m / min, and the coating thickness is 50-200 μm.

Citation Information

Cited By

  • Conductive material dispersion liquid, preparation method and application thereof, positive electrode and lithium secondary battery

    CN119725536A

  • Positive plate and lithium ion battery

    CN119786522A

  • Preparation method and application of lithium ion battery positive electrode slurry based on fluoride-free binder

    CN120657131A

  • Application of HNBR as lithium ion battery positive electrode binder, lithium ion battery positive electrode and lithium ion battery

    CN121307035A